2017
DOI: 10.14371/qih.2017.23.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Healthcare Accreditation Using a Systematic Review: Balanced Score Card Perspective

Abstract: Original Articles 의료기관인증의 효과에 대한 체계적 문헌고찰: Balanced Score Card 관점으로 2 Purpose: The purpose of this study was to analyze the impact of healthcare accreditation and to provide empirical evidence to validate positive effectiveness. Methods: Six electronic databases (KERIS, KoreaMed, NDSL, Ovid-medline, Embase, Cochrane library) were accessed in May 2016. Keywords used were 'accreditation' and 'Joint Commission on Accreditation of Healthcare Organization (JCAHO)'. Of the initially identified 3,008 articles, 60 stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 54 publications
2
10
0
Order By: Relevance
“…As an extension of previous reviews [ 13 , 31 , 32 , 34 ], our analysis did not find a correlation between accreditation and higher patient satisfaction or experience. The earlier presumption that patient satisfaction is a reverberation of hospital quality of service [ 120 ] was not confirmed in our review.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…As an extension of previous reviews [ 13 , 31 , 32 , 34 ], our analysis did not find a correlation between accreditation and higher patient satisfaction or experience. The earlier presumption that patient satisfaction is a reverberation of hospital quality of service [ 120 ] was not confirmed in our review.…”
Section: Discussionsupporting
confidence: 64%
“…On the one hand, positive impacts of hospital accreditation on organizational culture [ 12 , 32 , 34 ], clinical practice, organizational performance [ 23 ], clinical leadership, patient safety systems [ 28 ], quality of services [ 29 ], care delivery process [ 30 ], and efficiency [ 35 ] have been demonstrated. On the other hand, several reviews reported insufficient evidence pertaining to the impact of accreditation on measurable changes in quality of care [ 12 ], health outcomes [ 26 ], patient satisfaction [ 31 ], and economic outcomes [ 13 , 26 , 34 ]. For instance, Greenfield and Braithwaite [ 13 ] present diverging findings on the impact of accreditation as the effect was limited to promoting change and professional development, while on other impact categories such as quality measures, financial impact, and public disclosure results were inconclusive.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, in South Korea, patient safety has become a major focus in recent years, resulting in the initiation of a hospital accreditation program surveyed by the Korea Institute for Healthcare Accreditation (KOIHA) in 2010 to ensure patient safety and quality of care in Korean healthcare settings (KOIHA, n.d.). Many Korean hospitals have spent substantial funds and resources to prepare for the KOIHA survey, which appears to be effective in facilitating the improvement of patient safety (Kim, Jung, Kim, & Lee, ; Park, Jung, Park, Hwang, & Suk, ). Moreover, the KOIHA accreditation brought into focus the need for the education and training of nurses to enhance their patient safety competencies in their work (Hwang, ).…”
mentioning
confidence: 99%